2021
DOI: 10.1021/acs.est.1c01123
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanomaterial Fate in Plant Tissue: Nanoscale Impacts on Reproductive Tissues

Abstract: A thorough understanding of the implications of chronic low-dose exposure to engineered nanomaterials through the food chain is lacking. The present study aimed to characterize such a response in Cucurbita pepo L. (zucchini) upon exposure to a potential nanoscale fertilizer: copper oxide (CuO) nanoparticles. Zucchini was grown in soil amended with nano-CuO, bulk CuO (100 mg Kg–1), and CuSO4 (320 mg Kg–1) from germination to flowering (60 days). Nano-CuO treatment had no impact on plant morphology or growth nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…Additionally, pollen morphology and architecture and its chemical composition were also affected, such as accumulating the starch. Similar findings have previously reported that micro and nano-based metals can be phytotoxic to reproductive organs like reduced pollen germination, pollen tube growth, and minimize the viability of pollen grains as fertilization tools ( Kumbhakar et al, 2016 ; Marmiroli et al, 2021 ; Yoshihara et al, 2021 ). For instance, a decreased germination rate and tube elongation of pollen grains ( Lilium longiflorum ) exposed to 100 mg L –1 nZnO was observed in the in vitro condition ( Yoshihara et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, pollen morphology and architecture and its chemical composition were also affected, such as accumulating the starch. Similar findings have previously reported that micro and nano-based metals can be phytotoxic to reproductive organs like reduced pollen germination, pollen tube growth, and minimize the viability of pollen grains as fertilization tools ( Kumbhakar et al, 2016 ; Marmiroli et al, 2021 ; Yoshihara et al, 2021 ). For instance, a decreased germination rate and tube elongation of pollen grains ( Lilium longiflorum ) exposed to 100 mg L –1 nZnO was observed in the in vitro condition ( Yoshihara et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the observed unbalance fitness in pollen grains could be due to physiochemical alternations and also cytological aberrations during meiosis and mitosis processes, resulting in reduced pollen viability and consequently a higher mortality rate of seeds. In agreement with this, Marmiroli et al (2021) has recently reported some regulated pollen-specific genes in zucchini ( Cucurbita pepo L.) plants upon exposure to CuO nanoparticles. This study, along with data presented in this study, would strengthen the concept of NPs translocation into the floral parts and also trigger an NPs-specific response that has been proven somehow distinct from that induced by other counterparts (such as bulk and ion forms).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although there is a significant growth in the use of nanomaterials in contraception through the advantages of drug delivery and controlled drug release, the side effects of nanotoxicity on the human body cannot be ignored. For example, Cu-IUD, which is commonly used in contraception, is absorbed into the bloodstream through local mucosal tissues and induces hepatotoxicity and nephrotoxicity through mitochondrial failure, enhanced ketogenesis, fatty acid beta-oxidation, and glycolysis, resulting in scattered necrosis of hepatocytes and extensive necrosis of the proximal tubules of the kidney [ 173 ]. The second factor lies in the small size and surface charge of the nanomaterials, which can pass through the biological barrier, which reduces glutathione levels, inhibits catalase and superoxide dismutase activities to affect reproductive organs adversely [ 174 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of ATS for new organisms, endpoints, and span of variations in experimental scale and complexity have been increasingly functional in nanotoxicological literature through iterative processes able to combine results from physiological and molecular approaches [ 51 ]. Moreover, the monitoring of ENMs dispersal in the environment, especially at very early exposure stages and in realistic scenarios, can be further implemented [ 52 ] in accordance with the recently published EFSA guidance on risk assessment of the application of nanoscience and nanotechnologies in the food and feed chain, human and animal health, which considers in vitro/in vivo toxicological testing (e.g., in vitro degradation, toxicokinetics, genotoxicity, local and systemic toxicity), and the European Registration, Evaluation Authorization and Restriction of Chemicals (REACH) protocols for chemical safety assessment [ 1 , 53 ].…”
Section: Discussionmentioning
confidence: 99%